Perception on bioethics and animal welfare by veterinarians - Uliana, Daiana; Carvalho, Diego de; D'Agostini, Fernanda Maurer; Steffani, Jovani Antônio; Bonamigo, Elcio Luiz (Brazilian Journal of Veterinary Medicine, 2019)
The present study investigated veterinarians’ perceptions of bioethics and animal welfare training. Participants were divided in two groups: Group 1 graduated in or before 2003, and Group 2 graduated after 2003. One hundred forty participants completed the questionnaire: 62 (44.3%) from Group 1 and 78 (55.7%) from Group 2. One participant (1.6%) in Group 1 and 8 participants (10.2%) in Group 2 were taught bioethics as an elective or required course before graduating (p=0.003). Fifty-nine participants (95.2%) from Group 1 and 75 (96.2%) from Group 2 believed thata bioethics course should be required to graduate (p=0.959). Four participants (6.4%) from Group 1 and 24 (30.8%) from Group 2 were taught animal welfare as an elective or required course before graduating (p=0.003). Fifty-seven participants (91.9%) from Group 1 and 77 (98.7%) from Group 2 believed that animal welfare should be requiredto graduate(p=0.959). All participants considered both subjects highly relevant to the profession. Most participants were not taught bioethics or animal welfare courses before graduating; however, the availability of these courses increased after 2003. It was concluded that more emphasis should be given to teaching bioethics and animal welfare in veterinary undergraduate training.